Proceedings of the Fifth Joint Conference on Lexical and Computational Semantics 2016
DOI: 10.18653/v1/s16-2020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Modifier and Head Properties in Predicting the Compositionality of English and German Noun-Noun Compounds: A Vector-Space Perspective

Abstract: In this paper, we explore the role of constituent properties in English and German noun-noun compounds (corpus frequencies of the compounds and their constituents; productivity and ambiguity of the constituents; and semantic relations between the constituents), when predicting the degrees of compositionality of the compounds within a vector space model. The results demonstrate that the empirical and semantic properties of the compounds and the head nouns play a significant role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…This might explain the observed asymmetry. This finding is in line with earlier studies (Hätty, 2016;Schulte im Walde et al, 2016a) which investigated the asymmetry between the properties of heads and modifiers in noun-noun compounds. They showed that head constituent properties, such as their ambiguity or frequency, influence the predictability of NC compositionality to a much larger degree than modifier constituent properties.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This might explain the observed asymmetry. This finding is in line with earlier studies (Hätty, 2016;Schulte im Walde et al, 2016a) which investigated the asymmetry between the properties of heads and modifiers in noun-noun compounds. They showed that head constituent properties, such as their ambiguity or frequency, influence the predictability of NC compositionality to a much larger degree than modifier constituent properties.…”
Section: Resultssupporting
confidence: 93%
“…As to our knowledge, few systems have attempted to distinguish between word senses and then address various semantic relatedness tasks, such as Li and Jurafsky (2015) and Iacobacci et al (2015). Computational compositionality assessment has been studied for NCs (Reddy et al, 2011;Schulte im Walde et al, 2013;Schulte im Walde et al, 2016a) and PVs (McCarthy et al, 2003;Bannard, 2005;Kühner and Schulte im Walde, 2010). Most similar to our current work is Salehi et al (2015a), who addressed the problem of semantic ambiguity in MWEs by using a multi-sense skip gram model with two to five embeddings per word.…”
Section: Introductionmentioning
confidence: 99%
“…Only 18 of the 244 compounds occurred ≥100 times, which makes the results less conclusive. For this data set, we had access to the ranking of (Schulte im Walde et al, 2016a) and thus compare our results to theirs ((mod|head).vector in Table 3). Note that the numbers given here differ from those given in (Schulte im Walde et al, 2016a) because they are not calculated on the whole VDHB dataset but only on subsets of it.…”
Section: Germanmentioning
confidence: 99%
“…Thanks to the anonymous reviewers for their constructive comments and to Schulte im Walde et al (2016a) for sharing their results to enable a direct comparison.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…As to our knowledge, few systems have attempted to distinguish between word senses and then address various semantic relatedness tasks, such as Li and Jurafsky (2015) and Iacobacci et al (2015). Computational compositionality assessment has been studied for NCs (Reddy et al, 2011;Schulte im Walde et al, 2013;Salehi and Cook, 2013;Schulte im Walde et al, 2016a) and PVs (McCarthy et al, 2003;Baldwin et al, 2003;Bannard, 2005;Kühner and Schulte im Walde, 2010). Most similar to our current work is Salehi et al (2015a), who addressed the problem of semantic ambiguity in MWEs by using a multi-sense skip gram model with two to five embeddings per word.…”
Section: Introductionmentioning
confidence: 99%